PSVI-41 The comparative analysis of vaginal flora of high-productive cows in the postpartum period by Real-time PCR. (5th December 2019) - Korochkina, Elena A; Nechaev, Andrey; Stekolnikov, Anatoly; Nezhdanov, Anatoliy
Abstract: The aim of the study was the comparative analysis of species composition of vaginal bugs of high-productive cows (n = 7) in the postpartum period by Real-time PCR. The material were vaginal discharge of cows (four of them had acute pyogenic endometritis, another was apparently healthy). The vaginal discharge of sick cows contained the low count of bacteria Megasphaera spp., Veillonella spp., Dialister sрp., Lactobacillus spp. and streptococcus. The evaluation of bacterial count of Lachnobacterium spp., Clostridium spp., actinomycetes Atopobium spp., bacteria Staphylococcus spp., and yeast fungi Candida spр. did not demonstrate statistically different between groups. Probably this bacteria were not the etiological origin of postpartum endometritis of cows. However, vaginal discharge of cows with diagnosis acute pyogenic endometritis had high count of bacteria of Fusobacteriaceae (6, 0±3, 8 and 5, 3±2, 6 lg genomes/g), Enterobacteriaceae (6, 4±4, 1 and 5, 1±3, 0 lg genomes/g), bacteroides of Prevotella spp. and Porphyromonas spp. (7, 4±5, 2 and 6, 4±4, 4 lg genomes/g), actinomycetes Mobiluncus spp. and Corynebacterium spp. (5, 1±2, 5 and 4, 7±1, 9 lg genomes/g), Peptostreptococcus spp. and Eubacterium spp., in comparison with apparently healthy cows. The presence of this bacteria in the vaginal discharge of apparently healthy cows suggestive that this bacteria are the permanent vaginal flora. Thus, comparative analysis of the dysbiotic sort of vaginal flora of cows in postpartum period demonstrated that vaginal discharge of cows with diagnosis acute pyogenic endometritis consists the high count of bacteria of potentially pathogenic and pathogenic groups (Fusobacteriaceae, Enterobacteriaceae, Prevotella spp., Porphyromonas spp., Mobiluncus spp., Peptostreptococcus spp., Eubacterium spp.).